Exploring the Intrinsic Association Between Perceived Social Support and Depressive Symptoms and Problematic Phone Use Among College Students Based on Network Analysis - Gao E; Qi X; Liu M; Zhang Y; Li H (Psychology Research and Behavior Management)
Enze Gao,1 Xinru Qi,2 Min Liu,2 Ying Zhang,2 Hualing Li2 1Discipline Inspection Commission, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2School of Public Health, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Ying Zhang; School of Public Health, Xuzhou Medical University, Xuzhou, 221004, People’s Republic of China, Email 100002018044@xzhmu.edu.cn Hualing Li, School of Public Health, Xuzhou Medical University, Xuzhou, 221004, People’s Republic of China, Email lingling020198@126.comPurpose: A network analysis model was used to explore the complex associations between college students’ perceived social support and depressive symptoms and problematic phone use from a specific symptom perspective;.Methods: A total of 3869 study participants were included in this study using convenience sampling from five different universities in five different provinces in China. Perceived Social Support Scale was been used to measure the perceived social support level of college students, the extent of problematic smartphone use was evaluated using the Smartphone Addiction Scale-Short Version, and the Patient Health Questionnaire-9 scale to assess the depressive symptoms. A network analysis model was used to explore the intrinsic associations between their specific symptoms of perceived social support, depressive symptoms and problematic phone use;.Results: The results revealed that social support from family and from friends played a potentially critical role in alleviating depressive symptoms and reducing problematic phone use among college students;.Conclusion: The support given by family and peers is of great practical importance in reducing problematic cell phone use and controlling the development of depressive symptoms in the college population.Keywords: network analysis, perceived social support, depressive symptoms, problematic phone use